An extended Viner Model: Trade creation, diversion & reduction - Sören Prehn; Bernhard Brümmer; Thomas Glauben (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2012)
In this paper, we are going to reconsider the standard Viner Model [Viner, 1950] however under the premise of firm heterogeneity. By means of a graphical analysis we show that a consideration of the degree of firm heterogeneity is important for an evaluation of a preferential trade agreement. Depending on the degree of firm heterogeneity in the preferential country and the non-preferential country either a price increase and trade creation occurs or a price decrease and trade reduction. The standard Viner Model neither makes any predictions with regard to price changes nor can it explain trade reduction. The graphical analysis conducted here yields additional insights into the impacts of preferential trade agreements on trade.
Keywords: 330; International Trade; Preferential Trade Agreements; Viner Model; Firm Heterogeneity; Intensive Margin; Extensive Margin